2018
DOI: 10.21037/tlcr.2017.12.11
|View full text |Cite
|
Sign up to set email alerts
|

Radial endobronchial ultrasonography with distance measurement through a thin bronchoscope for the diagnosis of malignant peripheral pulmonary lesions

Abstract: Background: Peripheral pulmonary lesions (PPLs) are being discovered more frequently. We investigated efficiency, safety, and influencing factors in radial probe endobronchial ultrasound with distance measurement (rEBUS-D) using a thin bronchoscope during transbronchial biopsy (TBB) for the diagnosis of malignant PPLs. Methods:Patients with PPLs who underwent rEBUS were retrospectively analyzed. Cases with rEBUS-D and a gold-standard final diagnosis were considered.Results: rEBUS was completed in 589 cases; 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Moreover, Zhang et al's study22 suggested the diagnostic yield with R-EBUS with distance-measurement is not inferior to the yield with R-EBUS with GS. In studies with R-EBUS procedure with distance-measurement method, the reported diagnostic accuracy was 77%–87%111223 and we achieved an 80% diagnostic yield. Although R-EBUS-guided TBLB showed comparable accuracy to transthoracic needle biopsy24, the relatively high rate of false-negatives resulted in low negative predictive values (44%–46%), including in our study25.…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, Zhang et al's study22 suggested the diagnostic yield with R-EBUS with distance-measurement is not inferior to the yield with R-EBUS with GS. In studies with R-EBUS procedure with distance-measurement method, the reported diagnostic accuracy was 77%–87%111223 and we achieved an 80% diagnostic yield. Although R-EBUS-guided TBLB showed comparable accuracy to transthoracic needle biopsy24, the relatively high rate of false-negatives resulted in low negative predictive values (44%–46%), including in our study25.…”
Section: Discussionmentioning
confidence: 67%
“…Subsequently, 71 articles were selected for full text review. Forty records were excluded for the reasons presented in Figure 1, and 31 articles that met the defined inclusion criteria were finally included 5,14–43 …”
Section: Resultsmentioning
confidence: 99%
“…Forty records were excluded for the reasons presented in Figure 1 , and 31 articles that met the defined inclusion criteria were finally included. 5 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 …”
Section: Resultsmentioning
confidence: 99%
“…In particular, the EBUS-GS-TBB complication rate may have been underestimated in this study. Third, all EBUS-GS-TBB procedures were performed without the assistance of a navigation system, such as ENB, X-ray uoroscopy, or VB [35,36].…”
Section: Discussionmentioning
confidence: 99%